A Narrative Review of AI-Driven Omnichannel Branding Strategies in Global Digital Marketing - Satrio, Sello; Fatmawati, Yuli (Communica : Journal of Communication, 2024)
This narrative review explores the evolution of brand communication strategies within the digital marketing ecosystem, emphasizing the growing significance of omnichannel approaches and emerging technologies in building consumer engagement and brand loyalty. The review aims to evaluate how integrated communication practices—especially those employing artificial intelligence (AI), data-driven personalization, and immersive technologies like virtual reality (VR)—redefine consumer-brand interactions. Literature was collected through comprehensive searches in Scopus and Google Scholar using a Boolean-based strategy with keywords such as "digital marketing," "social media," "brand communication," and "consumer engagement." Inclusion criteria focused on peer-reviewed studies from the past five years that investigated digital branding strategies in developed and developing contexts. Results indicate that omnichannel brand strategies significantly outperform single-channel approaches by offering cohesive, multi-platform experiences that enhance loyalty and trust. AI-based personalization tools and VR-enabled brand experiences deepen user engagement by tailoring communication and delivering authentic interactions. However, the literature also highlights significant disparities in digital capacity across regions, with ethical issues like greenwashing and data privacy violations undermining consumer trust.  The findings suggest the need for policy-level interventions to promote sustainable, ethical, and inclusive brand communication. Stakeholders must align digital strategies with evolving consumer expectations and regulatory demands. Future research should explore the real-world efficacy of these tools and develop region-specific best practices to close the digital divide.